Increase the strength characteristics of polymer films by radiation graft polymerization; IOP Conference Series: Materials Science and Engineering; Vol. 168 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2016) - Rezvova M. A.; Zhevnyk V. D.; Pak V.; Denisov V. Ya.; Borodin Yu. V. Yuri Viktorovich (Adjacent to the main theme of the conference issues, 2017)
Title screen